Attenuating endothelial leakiness with self-assembled DNA nanostructures for pulmonary arterial hypertension. Issue 2 (4th January 2023) - Liu, Qian; Wu, Di; He, Binfeng; Ding, Xiaotong; Xu, Yu; Wang, Ying; Zhang, Mingzhou; Qian, Hang; Leong, David Tai; Wang, Guansong
Abstract : Self-assembled DNA is constructed to attenuate pulmonary vascular remodeling by restoring the endothelial barriers. Self-assembled DNA inhibits HPAEC growth by the Atg101/Beclin-1/VE-cadherin pathway. Abstract : Vascular endothelium dysfunction plays an important role in oncological and pulmonary diseases. Endothelial barrier dysfunction is the initial step of pulmonary vascular remodeling (PVR) and pulmonary arterial hypertension. Upregulation of a pro-autophagy protein Atg101 in the endothelial cells triggered a cascade of intracellular events that leads to endothelial dysfunction through apoptosis. Herein, we proposed a strategy that used endothelial targeting DNA nanostructures to deliver Atg101 siRNA (siAtg101) as a safe, biocompatible "band-aid" to restore pulmonary arterial endothelial barrier integrity within the intricate milieu of pulmonary cells and the pulmonary vasculature. The siAtg101 and aptamer conjugated DNA nanostructures were found to attenuate hypoxia-induced pulmonary endothelial leakiness with surprisingly high selectivity and efficacy. Further in vivo study revealed that functionalized DNA nanostructures likewise attenuated the vascular remodeling in a monocrotaline-induced PVR mouse model. Mechanistically, functionalized DNA nanostructures suppressed PVR by knocking down Atg101, which in turn, downregulated Beclin-1 and subsequently upregulated VE-cadherin to restore endothelial cells' adherin junctions. This work opened a new window for future nanomaterial design that directly addresses the interfacial endothelial cell layer that often stands between the blood and many diseased sites of nanotherapeutic interest.